The Effect of Eye-Hand Coordination Training on Improving The Service Skills of Tennis Athletes - Iraqi Maharani; Yadi Sunaryadi; Yudi Nurcahya; Mulyana (Universitas Negeri Semarang, 2025)
Service in tennis is a very important thing to determine the course of a game, players who often make mistakes in this process tend to experience a lack of self-confidence. Then it results in loss of concentration and unbalanced coordination. Players with fast hand reaction and hand-eye coordination who have high performance in every game. This study aims to determine the effect of hand-eye coordination training on improving the service skills of tennis athletes. The method used in this study is the Experimental method with a Pre-test Post-test Control group design design. The population used was 15 Indonesia University of Education Tennis Student Activity Unit athletes. Sampling was carried out by Purposive Sampling, and the sample numbered 8 people, then divided into 2 groups, namely the experimental group with Hand-Eye Coordination Training and Service Drills and the control group with Service Drill Training. In measuring the skills or accuracy of athletes using instrumentsHewitt tennis achievement test.Service Drill Training with Eye Hand Coordination and Service Drill Training have a significant influence on improving service skills. However, Service Drill Training with Eye Hand Coordination shows better results in improving the service skills of athletes in the sport of Tennis.